The Effect of Capital Structure on Profitability in Retail Trading Sub Sector Companies Listed on Idx In 2017-2021 - Ida Ayu Aurelia Agiestha (Journal of World Conference (JWC), 2022)
Capital structure and profitability is an important part for the company. Analysis of capital structure and profitability is needed for companies to find out how big the company's profit level is in a certain period. The purpose of this study was to determine how much influence capital structure has on the profitability of retail companies in Indonesia. This researcher uses a quantitative descriptive method. A sample of 32 companies with complete financial statements was taken by purposive sampling. The results show that the capital structure as measured by Debt-to-Equity Ratio (DER) and Debt to Total Assets (DAR) to profitability as measured by Return on Equity (ROE) has different results. The Debt-to-Equity Ratio (DER) shows a significant negative effect on Return on Equity (ROE). Meanwhile, Debt to Total Assets (DER) has no significant effect on Return on Equity (ROE).